Janus artificial cornea with instant and stable tissue adhesion and preparation method and application thereof

By adopting Janus artificial cornea in corneal transplantation technology, the cornea consists of a coating containing ε-PLL and 4-arm-PEG-NHS distributed on the collagen skeleton, it solves the complications caused by sutures and the problem that the material is difficult to balance between mechanical properties and optical transparency, achieving immediate, stable adhesion and optical transparency.

CN119564932APending Publication Date: 2025-03-07EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411703950.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In existing corneal transplantation techniques, the use of sutures leads to infection, complications and corneal tissue damage, and existing biomaterials are difficult to balance between mechanical properties and optical transparency.

Method used

Janus artificial cornea with instant and stable tissue adhesion was used, which consists of a coating containing ε-PLL and 4-arm-PEG-NHS distributed on the collagen backbone EB-Col. The molar ratio of functional group-NHS to -NH2 is 1: (0.6-1.4), and hydrogel cross-linking and tissue adhesion are achieved through amidation reaction.

Benefits of technology

It realizes the instant and stable adhesion ability of corneal repair materials, takes into account optical transparency and mechanical and adhesion properties, avoids suture-related complications, and adapts to a dynamic wet environment on the ocular surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119564932A_ABST
    Figure CN119564932A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and relates to a high-adhesion Janus artificial cornea as well as a preparation method and application thereof. The invention provides an artificial cornea, which is characterized in that a coating containing epsilon-PLL and 4-arm-PEG-NHS is distributed on a collagen skeleton EB-Col, and the functional group ratio of-NHS to-NH2 in the coating is 1: (0.6-1.4), and the molar ratio is 1: (0.6-1.4). The invention also relates to a corresponding high-adhesion Janus artificial cornea, and a preparation method and application thereof. The artificial cornea has instant and stable adhesion capability, gives consideration to optical transparency and mechanical and adhesion properties, can well adapt to the shape of a wound, is convenient to use, high in practical operability and mild in reaction, and is particularly suitable for being applied to cornea repair materials in the ophthalmology department, and the strong wet tissue adhesion property of the artificial cornea can adapt to a dynamic ocular surface moist environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and relates to a Janus artificial cornea with instant and stable tissue adhesion, and a preparation method and application thereof. Background Art

[0002] Corneal transplantation, commonly referred to as keratoplasty, involves the removal of the affected area of ​​the patient's cornea and its replacement with healthy corneal tissue from a donor. However, the use of sutures as a bonding method is not only time-consuming and requires a high level of skill, but is also associated with many potential complications after keratoplasty, including infectious keratitis, sterile infiltration, corneal neovascularization, and high astigmatism. For example, more than half of post-keratoplasty infections are related to the presence or removal of sutures. In addition, sutures often need to be removed later, which can cause damage to corneal tissue. For these reasons, sutureless keratoplasty is preferred to traditional corneal transplant techniques in some ways.

[0003] Biomaterials used for tissue engineering are divided into natural and synthetic, both of which have advantages and disadvantages. Natural biomaterials have the advantages of high biocompatibility, controllability, and specific functions at the molecular level. However, natural biomaterials are prone to cause immune responses, increase the chance of host rejection, and they degrade too quickly to provide sufficient and long-term mechanical support. Synthetic polymers can provide tissue adhesion, better mechanical properties, and relatively simple manufacturing than natural biomaterials, but low biological activity is a disadvantage of synthetic materials.

[0004] Natural materials and synthetic materials can be combined to comprehensively control their properties, which can improve material strength, bioadhesion and reduce biotoxicity. The strategy to achieve adhesion is to add components that provide tissue adhesion in the material design to achieve suture-free implantation. According to the application method of suture-free artificial corneal implants, they are divided into direct repair hydrogels and hydrogel adhesive patches. Direct repair hydrogels have the following shortcomings: (i) Insufficient mechanical strength: When hydrogels are subjected to external factors such as complex ocular environments (such as intraocular pressure and tear wash), it is difficult to maintain long-term stability and integrity, and they may shift, deform or degrade. At present, the long-term effects and safety of hydrogels have not been fully verified and there are still uncertainties. (ii) Unstable optical properties: Although many hydrogel materials are transparent, their optical properties may be reduced due to factors such as water content and refractive index, affecting vision recovery.

[0005] Based on the advancement of versatility and bionics, people have prepared hydrogel adhesive patches inspired by the natural structure and function of the cornea. It is a pre-prepared patch that is fixed to the corneal defect through its own adhesion ability or the action of an adhesive. Compared with directly adhered hydrogels, hydrogel adhesive patches have a specially designed adhesive layer and have the following advantages: (1) they can fit more tightly to the corneal tissue; (2) they have enhanced mechanical properties and provide a more stable repair effect. However, when designing such patches, researchers often cannot take into account (1) colorlessness and optical transparency; (2) irritating ingredients should be avoided; (3) violent triggering methods (excessive light radiation or heating) should be avoided; and (4) tissue adhesion performance must be stable to adapt to the dynamic wet environment to ensure long-term functionality and structural integrity. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an artificial cornea that can take into account both optical transparency and mechanical properties to ensure long-term stable and effective use.

[0007] The present invention provides a Janus artificial cornea with instant and stable tissue adhesion, wherein the Janus artificial cornea comprises: a coating containing ε-PLL and 4-arm-PEG-NHS is distributed on a collagen skeleton EB-Col, wherein the molar ratio of functional groups -NHS to -NH2 in the coating is -NHS:-NH2=1:(0.6-1.4);

[0008] The thickness of the Janus artificial cornea is 110-310 μm.

[0009] Furthermore, the thickness of the Janus artificial cornea is 150-180 μm.

[0010] Furthermore, the collagen skeleton EB-Col has one or more of the following characteristics:

[0011] The collagen skeleton EB-Col is cross-linked.

[0012] The curvature of the collagen skeleton EB-Col ranges from 7.8 to 8.5.

[0013] The thickness of the collagen skeleton EB-Col ranges from 100 to 300 μm.

[0014] Furthermore, EB-Col is cross-linked, and EB-Col is cross-linked by UV to increase its cross-linking density and enhance its mechanical properties. The curvature of EB-Col should match the curvature of the cornea. Preferably, the curvature of EB-Col ranges from 7.8 to 8.5. More preferably, the curvature of EB-Col is 7.9 to 8.2, for example, the curvature of EB-Col is 8.0, 8.1, 8.3, 8.4, etc.

[0015] Furthermore, in order to be used as an artificial cornea, the thickness of EB-Col should not be too thick or too thin. The research results of the present invention show that the range of EB-Col is 100 to 300 μm, which is more effective. More preferably, the thickness of EB-Col is preferably 150 to 190 μm. After the precursor solution is coated and volatilized, the thickness of the entire cornea is 160 to 200 μm, which can better achieve its function of replacing the cornea. Janus artificial cornea, also known as Janus (the two-faced god guarding the portal) membrane. Janus interface material refers to a material with asymmetric physical or chemical structures on both sides. Cell membranes, blood vessel walls, mucous membranes and skin in organisms all have Janus structural characteristics, which give them unique mass transfer, mechanical, barrier and protection properties, and can perform complex physiological tasks. Janus films with dense-porous asymmetric structures can guide anisotropic cell responses.

[0016] Furthermore, the molar ratio of the functional groups -NHS and -NH2 in the coating is -NHS:-NH2=1:(0.8-1.2). Furthermore, it is preferably 1:1.

[0017] On the other hand, the present invention also provides a method for preparing any of the above-mentioned Janus artificial corneas with immediate and stable tissue adhesion, comprising the following steps: dissolving ε-PLL and 4-arm-PEG-NHS in an ethyl acetate solution to form a precursor solution, and then applying the precursor solution to EB-Col to form a Janus artificial cornea. In the preparation process of the Janus artificial cornea coating of the present invention, the hydrophilicity of the PEG molecular chain promotes spontaneous reaction: multi-arm polyethylene glycol (PEG) derivatives with N-hydroxysuccinimide active ester groups (NHS) at the end can react spontaneously with nucleophilic amino groups without the need for external conditions such as light and heat. Hydrogel crosslinking and tissue adhesion are achieved by amidation reaction between -NHS and -NH2: under the triggering of water molecules, the -NHS on the 4-arm-PEG-NHS can undergo an amidation reaction with ε-PLL and -NH2 on the tissue surface, forming a -NHCO- covalent connection inside the hydrogel and at the interface in contact with the tissue. The cationic properties of ε-PLL impart antibacterial properties: the positive charge of ε-PLL interacts with the negative charge on the bacterial surface, leading to an imbalance in the charge on the bacterial surface, structural and functional destruction, and thus exhibiting broad-spectrum antibacterial activity.

[0018] Furthermore, when preparing the precursor solution, ε-PLL is first ground into powder, and then the ε-PLL powder and 4-arm-PEG-NHS are added to ethyl acetate to form a precursor solution. The ε-PLL in the coating is ground powder particles, and the particle size is too large, the formed film is not uniform, and the mechanical properties are also prone to defects. The particle size of the ground powder particles is not greater than 1 μm.

[0019] Furthermore, a precursor solution was prepared according to the ratio of 1-2 mL of ethyl acetate, 200 mg of 4-arm-PEG-NHS, and 2.4-8 mg of ε-PLL.

[0020] Further, according to 18 ~ 22mm 2 The EB-Col was coated with 18-22 μL of the precursor solution. After coating, the precursor solution was completely volatilized, and the coating was mainly composed of two components: ε-PLL and 4-arm-PEG-NHS.

[0021] Furthermore, the thickness of the coating should not be too thick or too thin. If the coating is too thick, excess hydrogel will overflow after being slightly pressed on the defective part of the ocular surface; if it is too thin, the cross-linking of the tissue surface will be unstable. In a preferred embodiment of the present invention, in an experiment conducted directly on a rabbit eyeball, 20 mm 2 The artificial cornea obtained by coating 20 μL of the prepared precursor solution on the film has very good performance. The coating thickness of the precursor solution on EB-Col is 5 to 15 μm, and more preferably 10 μm. In a preferred embodiment of the present invention, the thickness of the artificial cornea after coating is about 160 μm.

[0022] Furthermore, an EB-Col that matches the curvature and thickness of the natural cornea is constructed by an electrochemical assembly method, comprising the following steps:

[0023] (1) Preparation of type I collagen solution: Dissolve type I collagen in ultrapure water, dialyze to obtain a collagen solution with a concentration of 8 to 10 mg / mL, add hydrogen peroxide in a ratio of (10 to 20) by volume of the collagen solution to the hydrogen peroxide solution: 1, centrifuge to remove bubbles to obtain an electrolyte; the concentration of glacial acetic acid is in the range of (1 to 5):200;

[0024] (2) Preparation of type I collagen film: A three-electrode system was used, with a curved titanium sheet conforming to the curvature of the rabbit eyeball as the working electrode, a platinum wire as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The three-electrode system was immersed in an electrolyte and connected to an electrochemical workstation, and a constant current was applied to the electrodes for electrodeposition. After the electrodeposition was completed, a transparent collagen hydrogel film was obtained on the titanium sheet;

[0025] (3) Cross-linking of type I collagen membrane: riboflavin was dissolved in a 90% v / v ethanol-water solution with a mass concentration of 90% to 100%, and the solution was centrifuged and the upper layer of riboflavin was obtained as a clear yellow-green solution; the collagen membrane was placed in the clear yellow-green solution, and after cross-linking induced by 365 nm ultraviolet light overnight, the membrane was taken out and the residual riboflavin component was repeatedly washed with ultrapure water to obtain EB-Col.

[0026] In a third aspect, the present invention also provides the use of any of the above-mentioned Janus artificial corneas with immediate and stable tissue adhesion in the field of corneal repair. The artificial cornea of ​​the present invention has immediate and stable adhesion ability, takes into account optical transparency and mechanical and adhesion properties, and the bonding strength reaches 34kPa, can adapt well to the shape of the wound, is convenient to use, has strong practicality, and has a mild reaction. It is particularly suitable for use in ophthalmic corneal repair materials, and its strong wet tissue adhesion performance can adapt to the dynamic ocular surface moist environment.

[0027] Preferably, the Janus artificial cornea can be directly attached to the defect of the anterior corneal lamella to seal the defect, achieve corneal sealing repair or replace the entire cornea, with a haze of less than 30%, a transmittance of more than 80%, and good biocompatibility. For example, in a preferred embodiment of the present invention, the Janus artificial cornea is directly attached to the defect of the anterior corneal lamella of a rabbit to seal the defect and achieve corneal repair.

[0028] Preferably, the Janus artificial cornea promotes the adhesion, growth and / or diffusion of human corneal epithelial cells and inhibits bacterial growth and reproduction in a moist eye environment. In a preferred embodiment of the present invention, the Janus artificial cornea has bactericidal activity against the Gram-positive bacterium Staphylococcus aureus (S. aureus).

[0029] In the description of the present invention, the terms "comprises", "includes" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a reference structure" does not exclude the presence of other identical elements in the process, method, article or device including the element.

[0030] The beneficial effects of the present invention include:

[0031] (1) Mild reaction: In response to the problems of current hydrogel adhesive patches using irritating components and violent reactions during application, a Janus artificial cornea is developed that undergoes an ultra-fast and mild amidation reaction driven by moisture. Current hydrogel adhesive patch materials are usually cross-linked by ultraviolet light (UV), which has photochemical cytotoxicity and is harmful to DNA in the cornea and retina. Even the use of visible light cross-linking reactions is not clinically feasible for patients with keratitis. In addition, some other works use dopamine moieties to provide interface integrity functions, but at the same time also introduce unwanted colors into the material to interfere with vision. The artificial cornea of ​​the present invention can overcome the contradictory problems of membrane stability and transparency in the preparation process of these two materials, and is better suitable for scenarios that require partial filling or complete artificial corneas.

[0032] (2) Instant and stable adhesion: In view of the poor stability of hydrogel adhesives under wet dynamic conditions, a Janus artificial cornea was developed that can achieve instant (as short as 10 seconds) and stable adhesion to the corneal defect interface;

[0033] (3) Balancing optical transparency and mechanical and adhesion properties: In order to address the problem that current corneal repair materials sacrifice some transparency or even have slight color in pursuit of mechanical properties, we developed a colorless, highly transparent Janus artificial cornea with strong wet tissue adhesion properties to adapt to the dynamic moist environment of the ocular surface.

[0034] (4) Adaptability to wound shape: In order to address the problem that hydrogel adhesives cannot fully adapt to the thickness of the entire corneal defect, a Janus artificial cornea with an adhesive layer is developed that can fit more closely on the defective matrix. In addition, the present invention can adapt to daily traction of the cornea and provide a more stable repair effect.

[0035] (5) Easy to use and strong operability: Hydrogel adhesives require complex operations such as instant preparation and syringe application, while the Janus ACS developed by the present invention is based on a construction strategy of integrated engineering functions, which can achieve in-situ rapid bonding under moisture triggering, has low professional technical requirements for users, and is more practical;

[0036] (6) Innovation in material application: Traditional artificial corneas need to be combined with the recipient corneal bed using sutures, which is not only time-consuming and requires a high level of skills, but also can cause complications (infectious keratitis, sterile infiltration, corneal neovascularization and high astigmatism, etc.). The present invention uses the asymmetric physical structure and chemical composition of the Janus material to achieve suture-free implantation of damaged corneas. At the same time, unlike the current corneal repair materials that sacrifice some transparency or even have slight color in pursuit of mechanical and adhesion properties, the present invention is colorless, highly transparent and has strong wet tissue adhesion properties, and can adapt to the dynamic ocular surface wet environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, each drawing in the following description is for some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0038] Figure 1 Schematic diagram of EB-Col material preparation. (a) Using electrical signals to drive collagen molecules to self-assemble: Through the action of an external electric field, the positively charged collagen molecules in the collagen molecule solution migrate to the cathode, and at the same time, the cathode reduces H2O (or H2O2) to produce OH - And diffuse outward to neutralize the surrounding positively charged collagen molecules, which are assembled into a collagen gel membrane through hydrogen bonds and hydrophobic interactions; (b) The EB-Col material prepared using an electrode customized with the natural corneal curvature can be easily peeled off from the electrode surface.

[0039] Figure 2 Comparison diagrams of the present invention with different membrane materials: (a) SEM and TEM images of natural corneal stroma and EB-Col: The optical photographs show that EB-Col presents a highly transparent appearance similar to that of natural corneal stroma. Scanning electron microscopy (SEM) surface and cross-sectional microstructure analysis further showed that both the natural corneal stroma and EB-Col presented a tightly packed fibrous surface and densely stacked lamellar tissue, and high-power transmission electron microscopy (TEM) further showed that both the natural corneal stroma and EB-Col were composed of nano-scale fibrils; (b) Fiber diameter distribution histogram of the natural corneal stroma and EB-Col: EB-Col was composed of nano-scale microfibrils with a uniform diameter of about 8 nm, while the microfibrils of the natural corneal stroma were around 25 nm, indicating that EB-Col had finer collagen microfibrils than the natural corneal stroma; (c) Transmittance and haze of EB-Col in the visible light wavelength range: EB-Col had a higher transmittance (close to 90%) and a lower haze (less than 20%), while the transmittance of the natural corneal stroma was 78% at 600 nm, proving that the smaller diameter and packing density of nanofibrils can reduce light scattering and greatly improve the transparency of the natural polymer fibril matrix.

[0040] Figure 3 Schematic diagram of the preparation of Janus ACS and the process of in situ formation of an adhesion layer on its surface under wet conditions. (a) ε-PLL and 4-arm-PEG-NHS are fully mixed in ethyl acetate to prepare a precursor solution. Figure 3The optical photograph in shows that the precursor solution is then ultrasonically treated to allow for thorough mixing, and then the ethyl acetate is completely evaporated using a rotary evaporator to obtain dry Janus ACS; (b) In a humid environment, the active ester at the end of 4-arm-PEG-NHS of Janus ACS can undergo amidation reaction with the amino group on ε-PLL to form a layer of transparent and tough hydrogel.

[0041] Figure 4 Figure 2 shows the appearance and characterization of Janus ACS under dry and wet conditions, including macroscopic photos, SEM images and infrared characterization; (a) The optical photo of Janus ACS appears translucent under dry conditions. The microstructural analysis of the EB-Col surface and coating surface of Janus ACS by scanning electron microscopy (SEM) further shows that the structures of the EB-Col and coating surfaces are similar at a lower magnification, with no obvious difference. However, the closely arranged nano-scale ε-PLL powder can be seen on the coating surface after the magnification is increased; (b) Under wet conditions, Janus ACS forms a highly transparent gel layer. The SEM image shows that the EB-Col surface has no obvious change, and a hydrogel network is formed on the coating surface; (c) The infrared spectra of the EB-Col surface and the PEG-PLL coating surface of Janus ACS under dry and wet conditions are shown; compared with the dry Janus ACS, the wet Janus ACS does not observe the 1730 cm -1 The characteristic peak of C=O bond stretching at 1650cm -1 (amide I) and 1540 cm -1 (Amide II) shows two characteristic peaks of C=O stretching vibration and NH bending vibration, respectively. This result also proves that the adhesion is formed by amidation cross-linking between the active ester group at the end of PEG and the amino group on ε-PLL.

[0042] Figure 5 This is a comparison chart of the transmittance and haze of Janus ACS and EB-Col in the visible light wavelength range. It can be seen that Janus ACS has a similar transmittance to EB-Col, indicating that the construction of the hydrogel coating has almost no effect on the optical properties of the material. The haze of Janus ACS increases to a certain extent, but is also guaranteed to be at a low level (less than 30%).

[0043] Figure 6 Evaluation of the tissue adhesion performance of Janus ACS. (a) When triggered by a water environment, Janus ACS can form adhesion within 10 seconds and lift pig skin and various pig tissues; (b) Quantitative data of the tissue adhesion strength of Janus ACS.

[0044] Figure 7To further evaluate the tissue adhesion of Janus ACS, (a-c) lap shear test, 180° peel test and tensile test were performed. Janus ACS in different proportions showed ideal tissue adhesion ability, which was better than fibrin glue; (d) Anti-burst pressure: The burst pressure of Janus ACS was better than fibrin glue and much higher than the normal intraocular pressure; (f) After 3000 cycles of stretching, the pig eyeball sealed with Janus ACS still maintained a high anti-burst pressure of more than 50 kPa, showing good tissue sealing ability.

[0045] Figure 8 Figure 1 shows the results of in vitro biological evaluation of Janus ACS. (a) 24 hours after cells were seeded on the material, human corneal epithelial cells (HCECs) easily adhered and spread on Janus ACS, indicating that the material can well support the growth of HCECs. (b) The live / dead staining results on days 1, 3, and 5 showed that HCECs seeded on Janus ACS and cell culture plates continued to proliferate, and almost no obvious dead cells were observed during the culture period. (c) The CCK-8 test results showed that the cells seeded on the cell culture well plate control group and Janus ACS showed very high vitality on days 1, 3, and 5. (d) In vitro scratch test: HCECs seeded on Janus ACS began to migrate to the scratch area within 24 hours and completely filled the scratch area within 72 hours. The migration speed was significantly faster than that of the cell culture well plate control group. (e) The cell migration rate of HCECs on Janus ACS was significantly higher than that on the cell culture well plate, indicating that Janus ACS can promote cell migration, which is beneficial to the integration and repair of corneal tissue in vivo. (f) Antibacterial experiment: The EB-Col group and the EB-Col+PEG-NH2-NHS group had no bactericidal ability, and only a small amount of colonies were formed in the EB-Col+ε-PLL-PEG-NHS group, indicating that ε-PLL provided a certain bactericidal ability and had good antibacterial activity.

[0046] Fig. 9 Schematic diagram and real-life picture of the construction of the corneal lamellar defect model. An in vivo study was conducted using the New Zealand rabbit corneal lamellar transplantation model. An anterior lamellar corneal defect (5 mm in diameter, 250 μm in thickness) was mechanically excised from the New Zealand rabbit cornea. Then, Janus ACS was applied to the defect. After 10 seconds of immediate slight pressure, Janus ACS was cross-linked in situ and attached to the damaged matrix. Corneal injuries treated with commercial decellularized porcine corneal stroma (CM) were used as positive controls, and corneal injuries without material implantation were used as negative controls.

[0047] Fig.10Figure 2 shows the results of postoperative slit lamp biopsy. (a) The optical photograph shows that in the Janus ACS group, a clear boundary between the implant and the defect matrix was observed on the first day. On the 14th day, the boundary gradually became blurred, which may mean that the implant and tissue began to integrate. After 8 weeks, the boundary between the implant and the defect tissue was almost completely fused and difficult to distinguish clearly. During the entire 8-week observation period, the Janus The ACS group remained highly transparent throughout the whole process, and no immune response or neovascularization occurred. In comparison, the commercial porcine corneal stroma (CM) group showed a certain degree of turbidity after implantation, and neovascularization was observed on the 28th day. During the observation, white eye secretions were found hanging around the sutures, which may be the reason for the slower epithelialization process. No immune response was observed in the material-free implantation group, and the cornea remained transparent throughout the observation period. However, obvious corneal stroma defect with clear boundaries could still be observed 8 weeks after surgery. In addition, fluorescent staining images were taken by adjusting the slit lamp to cobalt blue filter mode to reflect the degree of epithelialization in different groups. The results showed that the area of ​​corneal epithelial defect in each group gradually shrank over time. At the 4th week after surgery, the material-free implantation group, Janus ACS group and CM group were all completely re-epithelialized. (b) During the entire recovery period, the Janus ACS group had a faster epithelialization rate than the CM group.

[0048] Fig.11Figure 1 shows an example of postoperative optical coherence tomography examination. (a) After implantation into the corneal defect, the corneal thickness of the Janus ACS group was restored and the corneal tissue curvature was well adapted. A clear boundary between the material and the tissue was visible. On day 14 after surgery, a thin white tissue membrane could be seen on the surface of the material, indicating that the material had begun to partially epithelialize, which was consistent with the observation results of fluorescent staining on day 14. At week 8 after surgery, complete corneal epithelium was formed on the Janus ACS, and the boundary between the material and the corneal stroma almost disappeared, indicating the integration between the material and the tissue. After implantation in the CM group, the corneal thickness thickened, but decreased on day 7, indicating that severe stroma edema occurred after implantation of the commercial decellularized porcine corneal stroma, which began to subside after one week. In addition, the situation after CM implantation was similar to that of the Janus ACS group. In contrast, the no-material implantation group also developed stromal edema within 7 days after surgery, which was consistent with the slit lamp observation results. Although the edema subsided after 14 days, the corneal thickness had not fully recovered to normal even at 8 weeks after surgery. (b) Corneal topography: The corneal topography of the no-material implantation group, healthy cornea group, Janus ACS group and CM group after 8 weeks was shown. The thickness of the no-material implantation group did not exceed 320 μm, indicating that the stromal layer had not recovered. The overall corneal thickness of the Janus ACS group was similar to that of the healthy cornea group. (c) Quantitative data of corneal thickness: The thickness of the healthy rabbit cornea was about 430 μm. The thickness of the Janus ACS group basically recovered to normal corneal thickness (423±17.39 μm), while the corneal thickness of the no-material implantation group was significantly lower than that of the healthy cornea group, with a central area thickness of about 283±8 μm. The central area thickness of the CM group was higher than that of the healthy cornea group, reaching 543±12.52 μm.

[0049] Fig.12 Figure 2 shows the analysis of foraging behavior. (a) New Zealand rabbit foraging behavior test; (b) Screenshot of foraging result video, showing that the Janus ACS group was able to quickly locate the bionic Timothy grass, similar to the healthy cornea group, while the CM group took longer to find the bionic Timothy grass, and the non-material implanted group was still searching in a chaotic manner; (c) Average time required for foraging. Quantitative data showed that the Janus ACS group foraged faster, showing a level similar to that of the healthy cornea group. This may be because the non-material implanted group still lacked more corneal stroma after surgery, while the corneal thickness of the CM group was significantly higher than that of the Janus ACS group and the healthy cornea group. Too thick or too thin central corneal thickness can cause refractive errors. DETAILED DESCRIPTION

[0050] Appropriate mechanical properties, transparency and adhesion properties are all prerequisites for suture-free corneal regeneration and repair materials. The electrical assembly technology of the present invention enables the collagen skeleton of the Janus artificial cornea to simulate the microstructure and tissue, as well as the macroscopic curvature and thickness of the natural corneal stroma, to achieve the desired transparency, refractive power and adaptive mechanics. On the surface of the Janus artificial cornea is a two-component "biocement" coating composed of ε-PLL and 4-arm-PEG-NHS. Driven by interfacial moisture, the coating undergoes an ultra-fast and mild amidation reaction and solidifies into a transparent gel layer, forming a stable covalent bond with the corneal stroma and the Janus artificial cornea scaffold, achieving instant (<10s) and stable tissue adhesion to adapt to the moist dynamic mechanical environment of the eye. The preparation and experimental result testing steps of the Janus artificial cornea developed by the present invention include:

[0051] 1. Preparation and characterization of Janus artificial cornea

[0052] 1. Preparation of EB-Col, the framework of Janus artificial cornea:

[0053] (1) Preparation of type I collagen solution: Type I collagen was fully dissolved in ultrapure water (8-10 mg / mL), placed in a dialysis bag and dialyzed in a glacial acetic acid solution (concentration range: (1-5):200) to obtain a collagen solution. Hydrogen peroxide was added in a ratio of (10-20):1 by volume of the collagen solution to the hydrogen peroxide solution, and the electrolyte was obtained by centrifugation to remove bubbles.

[0054] (2) Preparation of type I collagen membrane: The collagen solution was assembled using an electrochemical workstation: a three-electrode system was used, with a customized curved titanium sheet that conforms to the curvature of the rabbit eyeball as the working electrode (cathode), a platinum wire as the counter electrode (anode), and an Ag / AgCl electrode as the reference electrode. The three-electrode system was immersed in the electrolyte and connected to the electrochemical workstation. A constant current of 40 mA (6.67 mA / cm 2 ), deposition time 500s.

[0055] After the electrodeposition was completed, a transparent collagen hydrogel film (thickness of about 150 μm) was obtained on the titanium sheet. The center area of ​​the arc was taken out using a 5 mm trephine to obtain the collagen layer in the collagen Janus structure.

[0056] (3) Cross-linking of type I collagen membrane: Type I collagen membrane was cross-linked by UV-riboflavin, and the specific steps were as follows: 100 mg of riboflavin was dissolved in 100 mL of 90% v / v ethanol-water, and the upper clear yellow-green solution was taken after centrifugation (5000 r / min, 5 min). The collagen membrane was placed in the riboflavin solution, and after 24 h of cross-linking induced by 365 nm ultraviolet light, it was taken out and the residual riboflavin component was repeatedly washed with ultrapure water. The sample was recorded as EB-Col.

[0057] 2. Prepare ε-PLL-PEG coating precursor solution: first grind ε-PLL into powder, add ε-PLL and 4-arm-PEG-NHS into ethyl acetate (EA), and prepare ε-PEG-PLL precursor solution according to the ratio of 1 mL of ethyl acetate, 200 mg of 4-arm-PEG-NHS, and 2.4-8 mg of ε-PLL (functional group ratio -NHS:-NH2=1:(0.6-1.4)).

[0058] 3. Preparation of Janus artificial cornea: 20 μL of the above ε-PEG-PLL precursor solution was cast on EB-Col, and the Janus artificial cornea was obtained after vacuum drying at 45°C. The sample was recorded as Janus ACS.

[0059] 4. Characterization of microscopic morphology and chemical structure: Scanning electron microscopy (SEM, S4800 Hitachi) was used to observe the surface and cross-section of natural porcine cornea and EB-Col, and Fourier transform infrared spectrometer (FT-IR, Nicolet 5700, Thermo, USA) was used to verify the covalent connection of amide bonds formed between ε-PLL and PEG molecules in the Janus ACS coating surface.

[0060] 2. Characterization of the physical and chemical properties of Janus ACS

[0061] 5. Characterization of optical properties: EB-Col and Janus ACS were prepared according to the above method, immersed in PBS buffer for 1 h to reach saturated water content, and their transmittance (%) and haze (%) in the visible light wavelength range (380 nm to 780 nm) were detected using a UV-visible spectrophotometer (Lambda 950).

[0062] 6. Characterization of tissue adhesion strength: In order to evaluate the tissue adhesion ability of Janus ACS, a coating adhesion layer was also prepared on the other side of Janus ACS. According to the different contents of 4-arm-PEG-NHS and ε-PLL in the coating adhesion layer, the prepared Janus artificial corneas were named Janus ACS (1:1.4), Janus ACS (1:1), and Janus ACS (1:0.6), respectively. Janus ACS (12 mm × 9 mm) was adhered between two pieces of porcine tissue (40 mm × 10 mm), which was called the "sandwich" model.

[0063] The shear strength, interface toughness and tensile strength of pig skin were measured using a mechanical tensile machine (SANS CMT2503) and compared with commercial fibrin glue. The maximum force measured was defined as Fmax. The calculation methods of shear strength, interface toughness and tensile strength are as follows: shear strength = Fmax / adhesion area; interface toughness = 2Fmax / width of adhesion surface; tensile strength = Fmax / adhesion area

[0064] 7. Determination of anti-burst pressure: In order to explore the in vitro sealing ability of Janus ACS, Janus ACS with different coating contents were prepared according to the above method, and they were named Janus ACS (1:1.4), Janus ACS (1:1), and Janus ACS (1:0.6). A circular perforation with a diameter of 3 mm was created in the center of the cornea of ​​a fresh pig eyeball using a needle. After wiping off the leaked liquid, the perforation was sealed with Janus ACS. After 1 minute, a syringe was pushed by the syringe pump to inject a constant flow of artificial tears (30 mL / min) into the pig eyeball. The pressure was monitored by an electronic pressure gauge. The pressure at which the pressure gauge began to drop was the anti-burst pressure of Janus ACS.

[0065] 8. Adhesion stability test: In order to explore the adhesion stability of Janus ACS, an underwater cyclic tensile test was performed on a fresh pig eyeball sealed with Janus ACS, with the number of cycles set to 3000 and the displacement distance set to 6 mm. The bursting pressure of the pig eyeball was measured at different tensile cycle times.

[0066] 3. Evaluation of Janus ACS in vitro cell biocompatibility and antibacterial properties

[0067] 9. Cell adhesion and proliferation of human corneal epithelial cells (HCECs) on Janus ACS:

[0068] (1) Cell adhesion assay: The Janus ACS was cut into 10 mm discs using a hole puncher, placed in a 48-well plate, and sterilized by irradiation. Human corneal epithelial cells (HCECs) were inoculated onto the Janus ACS (5.0×10 4 / well), placed in a 37°C cell culture incubator (5% CO2) and cultured for 24 hours. After being fixed with 2.5% glutaraldehyde for 20 minutes, the material was washed twice with PBS, and dehydrated with 50%, 70%, 90%, 100%, and 100% anhydrous ethanol for 10 minutes each time. After dehydration, the material was placed in a 60°C oven for drying, and the cell morphology was observed by SEM (S-4800, Hitachi).

[0069] (2) Cell proliferation assay: Cells were inoculated according to the above method and cultured in a 37°C cell culture incubator (5% CO2). The cells were stained with Live / Dead cell dye on days 1, 3, and 5, protected from light throughout the process, and cell survival was observed using a confocal laser microscope (CLSM, Nikon A1R). CCK-8 cell viability assay (DOJINDO) was used to evaluate cell proliferation on days 1, 3, and 5.

[0070] (3) Cell scratch test: Cells were inoculated according to the above method and cultured in a 37°C cell culture incubator (5% CO2). After the cells were observed to be fully grown on the material by an inverted fluorescence microscope, a 200 μL pipette tip was used to scratch a mark on the material and the culture plate. At 0h, 24h, 48h, and 72h, the cell migration at the scratch was observed by an inverted fluorescence microscope and quantitatively analyzed by Image J, where the initial area of ​​the scratch was A0, and the area after migration was A1. The formula for calculating the cell migration rate was as follows: Cell migration rate (%) = (A1 / A0) × 100%.

[0071] 10. Evaluation of antibacterial performance: In order to explore the antibacterial effect of Janus ACS, the Gram-positive bacteria Staphylococcus aureus (S. aureus) was used in the experiment. The experiment was divided into four groups: blank group, EB-Col group, EB-Col + ε-PLL-PEG-NHS (Janus ACS) group, and E-BCol + PEG-NH2-PEG-NHS group. Three parallel samples were set up in each group. The EB-Col membrane, EB-Col + ε-PLL-PEG-NHS membrane (Janus ACS), and EB-Col + PEG-NH2-PEG-NHS membrane were cut into discs with a diameter of 6 mm and immersed in sterile saline. After the samples were irradiated and sterilized with cobalt-60 γ rays, 100 μL of bacterial solution (10 6 CFU / mL, 50% bacterial culture medium) was evenly dripped on the surface of the three groups of membrane materials and blank culture plates. After co-culture in a 37°C constant temperature incubator for 12 hours, the surface of the material was rinsed with physiological saline to collect bacteria. The number of remaining viable bacteria was calculated using the dilution plate method. Among them, C is the average number of viable bacteria in the blank group, and M is the average number of viable bacteria in the material group. The formula for calculating the antibacterial rate is as follows: Antibacterial rate = [(CM) / C] × 100%.

[0072] 6. Evaluation of corneal defect repair effect

[0073] Anterior lamellar corneal defect repair in New Zealand rabbits: An anterior lamellar corneal defect (5 mm in diameter, 250 μm in thickness) was mechanically excised from the New Zealand rabbit cornea, and Janus ACS was applied to the defect to evaluate the potential of Janus ACS in repairing corneal defects.

[0074] 10. Construction of rabbit corneal lamellar defect model and Janus ACS implantation: Two-month-old New Zealand rabbits were selected for in vivo animal experiments. The rabbits were anesthetized with sodium pentobarbital, the rabbit ocular surface was disinfected and local eye anesthesia was applied. Under a sterile environment, a 5mm diameter corneal trephine was used to construct a 250μm deep defect, a corneal scraper was used to remove the lamellar layer, and then a small amount of PB buffer was added to the defect. Janus ACS was attached to the defect position, and after gently pressing for 10s, Janus ACS was able to seal the defect. The commercial decellularized porcine corneal stroma group and the material-free implantation group were used as the positive control group and blank group, respectively.

[0075] 11. Postoperative slit lamp observation: The rabbit cornea was examined by slit lamp at 1 day, 1 week, 2 weeks, 4 weeks, and 8 weeks after surgery. Under the cobalt blue light mode, the rabbit corneal defect was stained with sodium fluorescein test paper to observe the recovery of corneal epithelial defect.

[0076] 12. Postoperative optical coherence tomography observation: AS-OCT was used to observe the recovery of the rabbit corneal epithelium and corneal thickness at five time points: 1 day, 1 week, 2 weeks, 4 weeks, and 8 weeks after surgery.

[0077] 13. Foraging behavior analysis: 24-26 days after corneal transplantation, rabbits were fed with timothy hay to build cognition, and then hunger and thirst were treated for 1 day to form appetite. 28 days after surgery, rabbits were allowed to forage. The experiment used bionic timothy hay to eliminate the influence of smell, and bionic flowers as interference group. The experiment was repeated with the positions of bionic timothy hay and bionic flowers exchanged to avoid accidental situations.

[0078] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0079] Example 1

[0080] Weigh 1 g of type I collagen and dissolve it in 100 mL of ultrapure water. Use a magnetic stirrer to fully stir the solution to completely dissolve the collagen, and obtain a transparent and viscous collagen solution.

[0081] Example 2

[0082] Hydrogen peroxide was added to the collagen solution and hydrogen peroxide solution prepared in Example 1 at a volume ratio of 10:1, and the mixture was thoroughly shaken and centrifuged to remove bubbles, thereby obtaining an electrolyte.

[0083] Example 3

[0084] The electrolyte prepared in Example 2 was assembled using an electrochemical workstation; a three-electrode system (CHI660E) was used, with a custom-made curved titanium sheet that conforms to the curvature of the rabbit eyeball as the working electrode (cathode), a platinum wire as the counter electrode (anode), and an Ag / AgCl electrode as the reference electrode. The three-electrode system was immersed in the electrolyte and connected to the electrochemical workstation, and a constant current was applied to the electrodes, set to 40 mA (6.67 mA / cm 2 ), deposition time 500s( Figure 1 a).

[0085] Example 4

[0086] After the electrodeposition is completed, the titanium sheet is removed from the electrolyte, and the excess electrolyte on the surface of the titanium sheet is removed by washing with ultrapure water. Then, the collagen film is peeled off from the surface of the titanium sheet with tweezers, and finally a transparent collagen hydrogel film (thickness is about 150 μm) is obtained ( Figure 1 b) Using a 5 mm trephine drill, the center area of ​​the arc was removed to obtain the collagen layer in the collagen Janus structure.

[0087] Example 5

[0088] The collagen membrane prepared in Example 4 was cross-linked by UV-riboflavin, and the specific steps were as follows: 100 mg of riboflavin was dissolved in 100 mL of 90% v / v ethanol-water solution, stirred to fully dissolve, and centrifuged (5000 r / min, 5 min) to obtain the upper clear yellow-green solution. The collagen membrane was placed in the riboflavin solution, and after 24 hours of cross-linking induced by 365 nm ultraviolet light, it was taken out and the residual riboflavin component was repeatedly washed with ultrapure water. The sample was recorded as EB-Col.

[0089] Example 6

[0090] First, ε-PLL was ground into powder, and ε-PLL and four-arm-polyethylene glycol-succinimidyl carbonate (4-arm-PEG-NHS) were added to ethyl acetate (EA) to prepare ε-PLL / PEG precursor solution ( Figure 3 a).

[0091] Example 7

[0092] The ε-PLL / PEG precursor solution prepared in Example 6 was poured onto the EB-Col prepared in Example 4, and the Janus artificial cornea was obtained after vacuum drying at 45°C. The sample was designated as Janus ACS ( Figure 3 a).

[0093] Example 8

[0094] The porcine cornea and EB-Col prepared in Example 5 were freeze-dried and observed on the surface and cross-section using a field emission scanning electron microscope (Nova Nano SEM 450). Both the natural corneal stroma and EB-Col showed a tightly packed fibrous surface and densely stacked layered tissue. The internal ultrastructure was observed using a transmission electron microscope (TEM, JEM-2100, JEOL). EB-Col had finer collagen microfibrils than the natural corneal stroma, which reduced light scattering and increased the light transmittance of EB-Col ( Figure 2 ).

[0095] Example 9

[0096] The Janus ACS prepared in Example 7 was freeze-dried and its microstructures on both sides under dry and wet conditions were observed using a field emission scanning electron microscope (Nova Nano SEM 450). The EB-Col surface and the coating surface had similar structures at a lower magnification, with no significant difference. However, when the magnification was increased, the coating surface could see densely arranged nano-scale ε-PLL powder ( Figure 4 a). However, under wet conditions, the EB-Col surface did not change significantly, and a hydrogel network was formed on the coating surface, indicating that Janus ACS formed a gel layer ( Figure 4 b).

[0097] Example 10

[0098] Attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) was performed on Janus ACS in EB-Col, dry state and wet state to detect the -1 Infrared spectrum of ε-PLL-PEG at 1730 cm -1 The C=O stretching vibration peak of 4-arm-PEG-NHS is lost at 1650cm -1 The C=O stretching vibration (amide I) and 1540 cm -1 The new peak of NH bending vibration (amide II) of PEG indicates that during the formation of ε-PLL hydrogel, the -NHS end of PEG and -NH2 in ε-PLL undergo amidation covalent crosslinking ( Figure 4 c).

[0099] Embodiment 11

[0100] The EB-Col prepared in Example 5 and the Janus ACS prepared in Example 7 were immersed in PBS buffer for 1 h to reach saturated water content. The transmittance (%) and haze (%) in the visible light wavelength range (380 nm to 780 nm) were detected by UV-visible spectrophotometer (Lambda 950). Janus ACS had a similar transmittance to EB-Col, indicating that the construction of the hydrogel coating had almost no effect on the optical properties of the material. The haze of Janus ACS increased to a certain extent, but was also guaranteed to be at a low level (less than 30%) ( Figure 5 ).

[0101] Example 12

[0102] In order to evaluate the tissue adhesion ability of Janus ACS, a coating adhesion layer was also prepared on the other side of Janus ACS. According to the different contents of 4-arm-PEG-NHS and ε-PLL in the coating adhesion layer, the prepared Janus artificial corneas were named Janus ACS (1:1.4), Janus ACS (1:1), and Janus ACS (1:0.6), respectively. Janus ACS (12mm×9mm) was adhered between two pieces of pig tissue (40mm×10mm), which was called the "sandwich" model. A mechanical tensile machine (SANSCMT2503) was used to measure the shear strength, interface toughness, and tensile strength of pig skin, and the results were compared with commercial fibrin glue. The results showed that the Janus ACS (1:1) group had the best tissue adhesion strength ( Figure 6 , 7 ).

[0103] Embodiment 13

[0104] In order to explore the in vitro sealing ability of Janus ACS, Janus ACS with different coating contents were prepared according to the same method as Example 11, and were named Janus ACS (1:1.4), Janus ACS (1:1), and Janus ACS (1:0.6), respectively. A circular perforation with a diameter of 3 mm was created in the center of the cornea of ​​a fresh pig eye using a 2 mm needle. After wiping off the leaked liquid, the perforation was sealed with Janus ACS. After 1 minute, a syringe pump was used to push the syringe into the pig eyeball to inject a constant flow of artificial tears (30 mL / min). The pressure was monitored by an electronic pressure gauge. The pressure at which the pressure gauge began to drop was the anti-burst pressure of Janus ACS. The results showed that the Janus ACS (1:1) group had the best anti-burst pressure ( Figure 7 d, e).

[0105] Embodiment 14

[0106] In order to explore the stability of Janus ACS adhesion, the Janus ACS (1:1) group with the maximum bursting pressure obtained in Examples 11 and 12 was used to perform an underwater cyclic tensile test on fresh pig eyeballs sealed with Janus ACS, with the number of cycles set to 3000 and the displacement distance set to 6 mm. The bursting pressure of pig eyeballs was measured at different tensile cycles, which proved that the pig eyeballs sealed with Janus ACS still maintained a high bursting pressure of more than 50 kPa, showing good tissue sealing ability ( Figure 7 f, g).

[0107] Note: In the experiments of the following examples, Janus ACS is used as an example with a ratio of Janus ACS (1:1).

[0108] Embodiment 15

[0109] In the cell adhesion experiment, Janus ACS was cut into 10 mm discs by a hole puncher, placed in a 48-well plate, and sterilized by irradiation. Human corneal epithelial cells (HCECs) were seeded on Janus ACS (5.0×10 4 / well), and placed in a 37°C cell culture incubator (5% CO2) for 24 hours. After fixing with 2.5% glutaraldehyde for 20 minutes, wash twice with PBS, and use 50%, 70%, 90%, 100%, and 100% anhydrous ethanol to dehydrate the material in a gradient manner, each time for 10 minutes. After dehydration, place it in a 60°C oven for drying, and observe the cell morphology by SEM (S-4800, Hitachi). 24 hours after the cells were inoculated on the material, human corneal epithelial cells (HCECs) easily adhered and spread on the Janus ACS, indicating that the material can well support the growth of HCECs ( Figure 8 a).

[0110] Example 16

[0111] In the cell proliferation and cell viability experiments, cells were inoculated according to the above method and cultured in a 37°C cell culture incubator (5% CO2). The cells were stained with Live / Dead cell dye on days 1, 3, and 5, and protected from light throughout the process. Cell survival was observed using a confocal laser microscope (CLSM, Nikon A1R), which showed that HCECs inoculated on Janus ACS and cell culture plates continued to proliferate, and almost no obvious dead cells were observed during the culture period ( Figure 8b). CCK-8 cell viability assay (DOJINDO) was used to evaluate cell proliferation on days 1, 3, and 5. 50 μL of CCK-8 was added to each well at a ratio of medium:CCK-8=10:1 (v / v), and after incubation for 2 hours, the well was taken out of the incubator, 100 μL was aspirated on a sterile bench and transferred to a 96-well plate. The OD value of each well at a wavelength of 450 nm (around 1.0) was detected using an ELISA reader. The results showed that the cells inoculated in the cell culture well plate control group and Janus ACS showed very high viability on days 1, 3, and 5. These results preliminarily proved that Janus ACS has good biocompatibility ( Figure 8 c).

[0112] Embodiment 17

[0113] Cell scratch test. Cells were inoculated according to the above method and cultured in a 37°C cell culture incubator (5% CO2). After the cells were observed to be fully grown on the material by inverted fluorescence microscopy, a 200μL pipette tip was used to scratch a mark on the material and the culture plate. At 0h, 24h, 48h, and 72h, the cell migration at the scratch site was observed by inverted fluorescence microscopy and quantitatively analyzed by Image J. The results showed that HCECs seeded on Janus ACS had begun to migrate to the scratch area within 24h and completely filled the scratch area within 72h. The migration speed was significantly faster than that of the cell culture well plate control group ( Figure 8 d, e).

[0114] Embodiment 18

[0115] In order to explore the antibacterial effect of Janus ACS, the experiment used Gram-positive bacteria Staphylococcus aureus (S. aureus). The experiment was divided into four groups: blank group, EB-Col group, EB-Col + ε-PLL-PEG-NHS (Janus ACS) group, and E-BCol + PEG-NH2-PEG-NHS group. Three parallel samples were set up in each group. The EB-Col membrane, EB-Col + ε-PLL-PEG-NHS membrane (Janus ACS), and EB-Col + PEG-NH2-PEG-NHS membrane were cut into 6 mm diameter discs and soaked in sterile physiological salt. After the samples were irradiated and sterilized with cobalt-60 γ rays, 100 μL of bacterial solution (10 6CFU / mL, 50% bacterial culture medium) was evenly dripped on the surface of the three groups of membrane materials and blank culture plates. After co-culture in a 37°C constant temperature incubator for 12 hours, the surface of the material was rinsed with saline to collect bacteria. The number of remaining live bacteria was calculated using the dilution plate method. The results showed that the EB-Col group and the EB-Col+PEG-NH2-NHS group had no bactericidal ability, and only a small amount of colonies were formed in the EB-Col+ε-PLL-PEG-NHS group, indicating that ε-PLL provided a certain bactericidal ability and had good antibacterial activity ( Figure 8 f).

[0116] Embodiment 19

[0117] Two-month-old New Zealand rabbits were selected for in vivo animal experiments. The rabbits were anesthetized with sodium pentobarbital, the ocular surface of the rabbits was disinfected and local eye anesthesia was applied. Under sterile conditions, a 5-mm-diameter corneal trephine was used to create a 250-μm-deep defect, and a corneal scraper was used to remove the lamellar layer ( Fig. 9 a, b).

[0118] Embodiment 20

[0119] A small amount of PB buffer was added to the defect, and Janus ACS was attached to the defect. After gently pressing for 10 seconds, Janus ACS was able to seal the defect ( Fig. 9 a, b).

[0120] Embodiment 21

[0121] The rabbit cornea was examined by slit lamp at 1 day, 1 week, 2 weeks, 4 weeks, and 8 weeks after surgery. Under cobalt blue light mode, the defective part of the rabbit cornea was stained with sodium fluorescein test paper to observe the recovery of corneal epithelial defect. Optical photos showed that in the Janus ACS group, a clear boundary between the implant and the defective stroma was observed on the first day, and on the 14th day, the boundary gradually became blurred, which may mean that the implant and tissue began to integrate. After 8 weeks, the boundary between the implant and the defective tissue was almost completely fused, and the boundary was difficult to distinguish clearly. During the entire 8-week observation period, the Janus ACS group remained highly transparent, and no immune response or new blood vessels appeared. In comparison, the commercial porcine corneal stroma (CM) group showed a certain degree of turbidity after implantation, new blood vessels were observed on the 28th day, and white eye secretions were found hanging around the sutures during the observation process, which may be the reason for the slower epithelialization process. No immune response was observed in the group without material implantation, and the cornea remained transparent throughout the observation period. However, a clear boundary of the corneal stroma defect could still be observed 8 weeks after surgery. In addition, fluorescent staining images were taken by adjusting the slit lamp to the cobalt blue filter mode to reflect the degree of epithelialization in different groups, with green representing epithelial defects. The results showed that over time, the area of ​​corneal epithelial defects in each group gradually shrank. At 4 weeks after surgery, the group without material implantation, the Janus ACS group, and the CM group were all completely re-epithelialized ( Fig.10 ).

[0122] Embodiment 22

[0123] The recovery of corneal epithelium and corneal thickness in rabbits was observed by optical coherence tomography (AS-OCT) at 1 day, 1 week, 2 weeks, 4 weeks, and 8 weeks after surgery. The results showed that after implantation into corneal defects, the corneal thickness of the Janus ACS group was restored and it could adapt well to the curvature of the corneal tissue, but a clear boundary between the material and the tissue could be seen. On the 14th day after surgery, a thin white tissue membrane could be seen on the surface of the material, indicating that the material had begun to partially epithelialize at this time, which was consistent with the observation results of fluorescent staining on the 14th day. At 8 weeks after surgery, complete corneal epithelium was formed on the Janus ACS, and the boundary between the material and the corneal stroma almost disappeared, indicating the integration between the material and the tissue. After implantation in the CM group, the corneal thickness thickened, but the thickness decreased on the 7th day, indicating that severe stromal edema occurred after implantation of commercial decellularized porcine corneal stroma, and the edema began to subside after one week. In addition, the situation after CM implantation was similar to that of Janus ACS. In contrast, the group without material implantation also developed stromal edema within 7 days after surgery, which was consistent with the slit lamp observation results. Although the edema subsided after 14 days, the corneal thickness did not fully return to normal even at 8 weeks after surgery ( Fig.11a). Corneal topography showed that the thickness of the non-material implanted group did not exceed 320 μm, indicating that the stroma had not recovered. The overall corneal thickness of the Janus ACS group was similar to that of the healthy cornea group ( Fig.11 b). Quantitative data of corneal thickness showed that the thickness of the healthy rabbit cornea was about 430μm. The thickness of the cornea in the Janus ACS group was basically restored to normal (423±17.39μm), while the thickness of the cornea in the non-material implanted group was significantly lower than that in the healthy cornea group, with a central thickness of about 283±8μm. The central thickness of the CM group was higher than that in the healthy cornea group, reaching 543±12.52μm ( Fig.11 c).

[0124] Embodiment 23

[0125] 24-26 days after the corneal transplantation, the rabbits were fed with timothy hay to build cognition, and then they were given a day of hunger and thirst treatment to build appetite. 28 days after the operation, the rabbits were allowed to forage for food. The experiment used bionic timothy hay to eliminate the influence of smell, and bionic flowers as interference group. The experiment was repeated with the positions of bionic timothy hay and bionic flowers swapped to avoid accidental situations ( Fig.12 a). The results showed that the Janus ACS group was able to quickly locate the bionic Timothy grass, similar to the healthy cornea group, while the CM group took longer to find the bionic Timothy grass, and the non-material implant group was still searching in a chaotic manner ( Fig.12 b). Quantitative data of the average time taken by all rabbits to find the bionic timothy grass showed that the Janus ACS group had a faster foraging speed, showing a similar level to the healthy cornea group. This may be because the non-material implanted group still lacked a large amount of corneal stroma after surgery, and the corneal thickness of the CM group was significantly higher than that of the Janus ACS group and the healthy cornea group. Too thick or too thin central corneal thickness can cause refractive errors ( Fig.12 c).

[0126] The above description of the embodiments is to facilitate the understanding and use of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A Janus artificial cornea with immediate and stable tissue adhesion, characterized in that: The Janus artificial cornea is: a coating containing ε-PLL and 4-arm-PEG-NHS is distributed on the collagen skeleton EB-Col, and the molar ratio of the functional groups -NHS and -NH2 in the coating is -NHS:-NH2=1:(0.6-1.4); The thickness of the Janus artificial cornea is 110-310 μm.

2. The Janus artificial cornea with immediate and stable tissue adhesion according to claim 1, characterized in that: The thickness of the Janus artificial cornea is 150-180 μm.

3. The Janus artificial cornea with immediate and stable tissue adhesion according to claim 1, characterized in that: The collagen skeleton EB-Col has one or more of the following characteristics: The collagen skeleton EB-Col is cross-linked. The curvature of the collagen skeleton EB-Col ranges from 7.8 to 8.

5. The thickness of the collagen skeleton EB-Col ranges from 100 to 300 μm.

4. The Janus artificial cornea with immediate and stable tissue adhesion according to claim 1, characterized in that: The molar ratio of the functional groups -NHS and -NH2 in the coating is -NHS:-NH2=1:(0.8-1.2).

5. A method for preparing a Janus artificial cornea with immediate and stable tissue adhesion as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following steps: dissolving ε-PLL and 4-arm-PEG-NHS in ethyl acetate solution to form a precursor solution, and then coating the precursor solution on EB-Col to form a Janus artificial cornea.

6. The method for preparing a Janus artificial cornea with immediate and stable tissue adhesion according to claim 5, characterized in that: When preparing the precursor solution, ε-PLL is firstly ground into powder, and then the ε-PLL powder and 4-arm-PEG-NHS are added into ethyl acetate to form a precursor solution.

7. The method for preparing a Janus artificial cornea with immediate and stable tissue adhesion according to claim 6, characterized in that: The precursor solution was prepared according to the ratio of 1-2 mL of ethyl acetate: 200 mg of 4-arm-PEG-NHS: 2.4-8 mg of ε-PLL.

8. The method for preparing a Janus artificial cornea with immediate and stable tissue adhesion according to claim 5, characterized in that: According to 18~22mm 2 EB-Col was coated using a ratio of 18 to 22 μL of the precursor solution.

9. The method for preparing a Janus artificial cornea with immediate and stable tissue adhesion according to claim 5, characterized in that: The electrochemical assembly method is used to construct an EB-Col that matches the natural corneal curvature and thickness, including the following steps: (1) Preparation of type I collagen solution: Dissolve type I collagen in ultrapure water, dialyze to obtain a collagen solution with a concentration of 8 to 10 mg / mL, add hydrogen peroxide in a ratio of (10 to 20) by volume of the collagen solution to the hydrogen peroxide solution: 1, centrifuge to remove bubbles to obtain an electrolyte; the concentration of glacial acetic acid is in the range of (1 to 5):200; (2) Preparation of type I collagen membrane: A three-electrode system was used, with a curved titanium sheet conforming to the curvature of the rabbit eyeball as the working electrode, a platinum wire as the counter electrode, and an Ag / AgCl electrode as the reference electrode. The three-electrode system was immersed in an electrolyte and connected to an electrochemical workstation, and a constant current was applied to the electrodes for electrodeposition; After the electrodeposition, a transparent collagen hydrogel film was obtained on the titanium sheet; (3) Cross-linking of type I collagen membrane: riboflavin was dissolved in a 90% v / v ethanol-water solution with a mass concentration of 90% to 100%, and the solution was centrifuged and the upper layer of riboflavin was obtained as a clear yellow-green solution; the collagen membrane was placed in the clear yellow-green solution, and after being cross-linked overnight under 365 nm ultraviolet light, the membrane was taken out and the residual riboflavin component was repeatedly washed with ultrapure water to obtain EB-Col.

10. Use of the Janus artificial cornea with immediate and stable tissue adhesion as claimed in any one of claims 1 to 4 in the field of corneal repair.

Citation Information

Cited By

  • Biological adhesive with stable performance as well as preparation method and application of biological adhesive

    CN120678982A